Growth and Survival of Thai Climbing Perch (Anabas testudineus) and Snakeskin Gourami (Trichogaster pectoralis) Reared in Brackish Water in Cement Pond in Salt-affected Soil - Noinumsai, Napat; Saengsanga , Thanakorn; Kosanlavit, Waraporn (Journal of Food Health and Bioenvironmental Science, 2023)
Thai climbing perch (Anabas testudineus) and snakeskin gourami (Trichogaster pectoralis) are freshwater fish species commercially grown in Southeast Asian countries. This research investigated survival rate and growth performances of Thai climbing perch and snakeskin gourami when cultured in brackish water (7.50 ppt) in salt affected soil. The experiment was conducted in a brackish water cement ponds for 6 months. Water quality was also measured at 2-month intervals. The results found that average daily weight gain (DWG) of Thai climbing perch and snakeskin gourami was 0.597±0.017 and 0.048±0.010 g/day, respectively. Co-culture between the fish species had a DWG of 0.592± 0.022 and 0.038±0.004 g/day for Thai climbing perch and snakeskin gourami, respectively. At the end of the study, the productivity of Thai climbing perch weight was 121.67±2.89 kg and snakeskin gourami weight was 24.15±2.10 kg. In addition, higher survival rate of 93.11±4.07% for Thai climbing perch and 52.00±17.02% for snakeskin gourami (T3) reared in brackish water was obtained in co-culture system (T3) compared with Thai climbing perch (T1, 87.33 ± 5.78%) and snakeskin gourami (T2, 43.89±15.87 %). Water quality at the end of the experimental period found the difference in each treatment. The results showed that T1 found the highest values of many water quality parameters. This study highlights the culture of freshwater fish in brackish water has advantages for fish farming in salt affected soil.